2023
DOI: 10.4102/aveh.v82i1.780
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconic patient profile and management at public sector facilities in South Africa

Abstract: Background: Keratoconus (KC) is a condition marked by thinning and protrusion of the cornea resulting in high myopia and irregular astigmatism. Knowledge of KC patients’ profiles and management approaches used can help to predict the needs of public hospitals to improve patient care.Aim: This study aimed to describe the profiles and management of KC patients.Setting: Capricorn district, Limpopo Province, South Africa.Methods: Medical records of 188 KC patients attending public hospitals of Capricorn District f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“… 13 Keratoconus is a bilateral but asymmetrical condition; therefore, many patients usually seek consultation when vision in the better eye has deteriorated, and by that time they would have had significant vision reduction in the worst eye. 39 In this study, many patients reported disruption in their normal performance of daily activities as they could no longer see well the writings on the board in school, some had to work more than the average learner so as to be on par with peers, some worked slower than they used to and others had to drop out of school. This affected their QoL and forced them to have some dependence on other people to cope with daily activities.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“… 13 Keratoconus is a bilateral but asymmetrical condition; therefore, many patients usually seek consultation when vision in the better eye has deteriorated, and by that time they would have had significant vision reduction in the worst eye. 39 In this study, many patients reported disruption in their normal performance of daily activities as they could no longer see well the writings on the board in school, some had to work more than the average learner so as to be on par with peers, some worked slower than they used to and others had to drop out of school. This affected their QoL and forced them to have some dependence on other people to cope with daily activities.…”
Section: Discussionmentioning
confidence: 71%
“…Patients in these facilities were detected at very late stages when signs such as Munson’s sign were visible due to lack of knowledge, skills and basic equipment. 39 In addition, only a half (54.2%) of the optometrists in these facilities self-reported to have adequate knowledge and skills to screen, examine, diagnose and manage KC. 16 Poor knowledge and skills of practitioners could have contributed to poor patient education and consequently poor health literacy, 40 hence the lack of knowledge of KC as described in the study by Baenninger et al 38 …”
Section: Discussionmentioning
confidence: 99%
“…Patients in these facilities were detected at very late stages when signs such as Munson's sign were visible due to lack of knowledge, skills and basic equipment. 39 In addition, only a half (54.2%) of the optometrists in these facilities self-reported to have adequate knowledge and skills to screen, examine, diagnose and manage KC. 16 Poor knowledge and skills of practitioners could have contributed to poor patient education and consequently poor health literacy, 40 hence the lack of knowledge of KC as described in the study by Baenninger et al 38 The description of KC by patients using words like the 'eye having cracks' or the eye having a 'rugby ball shape' insinuates limitations in healthcare vocabulary, especially for native speakers who need to provide descriptions of the eye conditions.…”
Section: Discussionmentioning
confidence: 99%